PENGARUH PENGEMBANGAN KARIR DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI PADA PUSKESMAS MANGASA DI MAKASSAR - Muhammad Carda P (Jurnal Bisnis dan Kewirausahaan, 2019)
This study aims: 1) to analyze the effect of career development on employee job satisfaction at the Mangasa Health Center in Makassar, 2) to analyze the influence of the organizational climate on employee job satisfaction at the Mangasa Health Center in Makassar. This research uses a multiple regression analysis method. The research data used were obtained from interviews, documentation and questionnaires. The results of this study indicate that: 1) based on the results of multiple regression tests, the influence of career development variables has a positive and significant effect on job satisfaction of employees of the Mangasa Health Center in Makassar. Career development at the Mangasa Health Center in Makassar is basically an increase in employee performance that reflects the ability of the organization in work, meaning that the performance of each employee is rated and measured in terms of values ​​and criteria determined by the organization, and 2) based on the results of multiple regression tests, the influence of organizational climate variables has a positive and significant effect on job satisfaction of Mangasa Health Center employees in Makassar. Employee job satisfaction at the Mangasa Health Center in Makassar can occur if employees feel they have a feeling of justice in doing work. An organizational climate that is considered fair will encourage employees to immediately achieve satisfaction at work